2016
DOI: 10.37236/5095
|View full text |Cite
|
Sign up to set email alerts
|

Graphs with Induced-Saturation Number Zero

Abstract: Given graphs $G$ and $H$, $G$ is $H$-saturated if $H$ is not a subgraph of $G$, but for all $e \notin E(G)$, $H$ appears as a subgraph of $G + e$. While for every $n \ge |V(H)|$, there exists an $n$-vertex graph that is $H$-saturated, the same does not hold for induced subgraphs. That is, there exist graphs $H$ and values of $n \ge |V(H)|$, for which every $n$-vertex graph $G$ either contains $H$ as an induced subgraph, or there exists $e \notin E(G)$ such that $G + e$ does not contain $H$ as an induced subgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Using the structural descriptions of the classes Forb(C 4 , C 4 , P 4 ) (due to Chvátal and Hammer [2]) and Forb(C 4 , C 4 , C 5 ) (due to Földes and Hammer [6]), Behrens et al [1] showed that there is no graph G so that G → → {C 4 , C 4 , P 4 } or G → → {C 4 , C 4 , C 5 }. The later example shows that even though there are graphs G 1 , G 2 , G 3 so that G 1 → → C 4 , G 2 → → C 4 and G 3 → → C 5 , there is no induced-saturated graph for the family {C 4 , C 4 , C 5 }.…”
Section: Further Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the structural descriptions of the classes Forb(C 4 , C 4 , P 4 ) (due to Chvátal and Hammer [2]) and Forb(C 4 , C 4 , C 5 ) (due to Földes and Hammer [6]), Behrens et al [1] showed that there is no graph G so that G → → {C 4 , C 4 , P 4 } or G → → {C 4 , C 4 , C 5 }. The later example shows that even though there are graphs G 1 , G 2 , G 3 so that G 1 → → C 4 , G 2 → → C 4 and G 3 → → C 5 , there is no induced-saturated graph for the family {C 4 , C 4 , C 5 }.…”
Section: Further Resultsmentioning
confidence: 99%
“…In fact, Martin and Smith (2012) showed that there is no P 4 -induced-saturated graph. Behrens et al (2016) proved that if H belongs to a few simple classes of graphs such as a class of odd cycles of length at least 5, stars of size at least 2, or matchings of size at least 2, then there is an H-induced-saturated graph.This paper addresses the existence question for H-induced-saturated graphs. It is shown that Cartesian products of cliques are H-induced-saturated graphs for H in several infinite families, including large families of trees.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Martin and Smith [6] introduced the notion of induced saturation on trigraphs. As a special case of this more general framework, there arises the notion of inducedsaturated graphs, first studied in its own right by Behrens et al [2] and later also by Axenovich and Csikós [1]. Given graphs G, H, we say G is H-induced-saturated if G contains no induced subgraph isomorphic to H, but deleting any edge of G creates an induced subgraph isomorphic to H, and adding any new edge to G from G c also creates an induced subgraph isomorphic to H. Throughout the rest of the note, we will abbreviate a H-induced-saturated graph as a H-IS graph.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the notion of trigraphs, Prömel and Steger [12] and Martin and Smith [11] defined the induced subgraph version of the Turán number and the saturation number, respectively, of a given graph. We omit the exact definitions here, see [2,3,7,9] for more details and other recent work on Turán-type problems concerning induced subgraphs.…”
Section: Introductionmentioning
confidence: 99%